2014
DOI: 10.1097/imi.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Delivery of a Novel Direct Epicardial Assist Device in a Porcine Heart Failure Model

Abstract: Objective Despite advances in design, modern ventricular assist device placement involves median sternotomy and cardiopulmonary bypass and is associated with infectious/embolic complications. In this study, we examine the feasibility and function of a novel minimally invasive, non–blood-contacting epicardial assist device in a porcine ischemic cardiomyopathy model. Methods Feasibility was first tested in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The final goal of this study was to follow the route of recently proposed epicardial contraction assist devices. 35 Because external ventricular compression is the most physiological way to improve pump function, 36,37 as proposed by recent preclinical investigations, 38 we tested our fittest material, M1CL1, in an experimental setting where cardiac muscle contraction was supported by the LCE working in parallel with a mouse cardiac trabecula ( Figure 5). The sum of the parallel forces compared with that developed by the muscle alone demonstrated that our LCE strips provided a significant systolic assistance.…”
Section: Lce To Assist Cardiac Contractionmentioning
confidence: 99%
“…The final goal of this study was to follow the route of recently proposed epicardial contraction assist devices. 35 Because external ventricular compression is the most physiological way to improve pump function, 36,37 as proposed by recent preclinical investigations, 38 we tested our fittest material, M1CL1, in an experimental setting where cardiac muscle contraction was supported by the LCE working in parallel with a mouse cardiac trabecula ( Figure 5). The sum of the parallel forces compared with that developed by the muscle alone demonstrated that our LCE strips provided a significant systolic assistance.…”
Section: Lce To Assist Cardiac Contractionmentioning
confidence: 99%
“…Because local infarct restraint intends to prevent infarct expansion most of which occurs early post-MI, the majority of scaffolds, patches and devices evaluated have been implanted immediately post-MI [17,18,19,42,58,59,60,61,62]. However, some groups have seen benefits in cardiac function upon patch implantation at latter timepoints post-MI [63,64,65,66,67,68,69,70] ranging from four days to 12 weeks (Figure 3).…”
Section: Optimizing Local Reinforcement: Multifunctional Biomimetmentioning
confidence: 99%
“…At implantation eight weeks into IMR, the adjustment of the device was done such that IMR was minimized and in a chronic study the group showed that this initial mechanical reinforcement led to a reduction of end-systolic and diastolic LV volumes. Another group pursued a study to test if the minimally invasive delivery of an inflatable localized device to treat ICM was feasible [70]. Their device was made of a heavy-duty 2.5 × 2.5 cm neoprene rubber inflatable bladder that was positioned centrally within the infarct and then secured to the surrounding border zone myocardium with polypropylene mesh.…”
Section: Optimizing Local Reinforcement: Multifunctional Biomimetmentioning
confidence: 99%
See 1 more Smart Citation